1995
DOI: 10.1080/00405009508631309
|View full text |Cite
|
Sign up to set email alerts
|

The Friction Couple in Yarn Bending

Abstract: Yarn bending can be characterised by a flexural rigidity B and a friction or coercive couple M . This paper describes an analysis of M^^ in Icrms of filament properties, yarn twist and yarn tex. Some limited experimental data are presented in support of thc result of the analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The bending properties determine the handling performance of fabrics. 1921 The BAR and BW values in both the warp and weft directions and outer and inner surfaces of the prepared cotton/chitosan fabric samples were recorded and are shown in Figure 5 and Table 4. There were strong negative correlations between BAR and chitosan blend ratio (BARa, r = −.815, p < 0.01; BARe, r = −.651, p < 0.01), and BW and chitosan blend ratio (BWa, r = −.849, p < 0.01; BWe, r = −.723, p < 0.01) (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…The bending properties determine the handling performance of fabrics. 1921 The BAR and BW values in both the warp and weft directions and outer and inner surfaces of the prepared cotton/chitosan fabric samples were recorded and are shown in Figure 5 and Table 4. There were strong negative correlations between BAR and chitosan blend ratio (BARa, r = −.815, p < 0.01; BARe, r = −.651, p < 0.01), and BW and chitosan blend ratio (BWa, r = −.849, p < 0.01; BWe, r = −.723, p < 0.01) (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…This lack of fit probably results from the many assumptions made concerning the twine mechanics and the netting construction. Other studies have demonstrated that the assumption that bending moment is proportional to curvature is unlikely to hold for the twines used in the manufacture of fishing gears, where there will be friction between the component fibres, which are likely to bend non-linearly and move over each other (Leaf, 1995). Therefore, the regression equations above may not represent the physical situation accurately enough to obtain good estimates of all five parameters.…”
Section: Discussionmentioning
confidence: 97%
“…and A7. + dM_ d e to the yam bending on the plane Oxy, with their vect rial directions along the axis z; and the socalled &dquo;c rcive&dquo; or &dquo;friction&dquo; moment M~, and Mo + dMo ue to the bending tendency caused by the compone t of yam torsional moment Q in the y direction [6]. The equations of the equilibrium for moments acting on the yatn element ds are then In Equation 4, the component of yam torsional moment Q ir1 the y direction, (~j3, tends only to bend the yam element on the plane Oxz.…”
mentioning
confidence: 99%
“…In the absence of any equation of yam coercive moment Mo for rotor spun yarns, it is reasonable to suppose that Leaf's equations [6] from his filament yarn model, which is similar to the ideal yam model [5], are also applicable for rotor spun yam. This is because the effect I of wrapping fibers is eliminated by introducing the correction factor c f to account for the number of fibers in the core part of the rotor spun yam.…”
mentioning
confidence: 99%